Empyema caused by a colopleural fistula: A case report. Issue 39 (September 2017) - Lian, Rui; Zhang, Guochao; Zhang, Guoqiang
Abstract: Ratinale: Empyema is a condition in which pus gathers in the area between the lungs and the inner surface of the chest wall. An empyema caused by colo-pleural fistula is a rare but potentially life-threatening condition. Patient concerns: We describe a case of 42-year-old man was brought to our Emergency Department for chest pain with dyspnea and fever. Diagnoses: The final diagnoses are empyema caused by colo-pleural fistula and colon cancer. Interventions: The patient underwent laparotomy surgery, during which a tumor was found in the splenic flexure of the descending colon. The tumor penetrated the colonic serosa and invaded the left side of the diaphragm. A left hemicolectomy was performed. Outcomes: After the operation, the patient recovered smoothly and was discharged on postoperative day 14. It's been over 3 years now, CT and colonoscopy assessments show no recurrence or metastasis. Lessons: This case serves as a reminder to test for pathogens in patients with an unexplained empyema. If normal intestinal bacteria are detected, the empyema may be derived from intestinal disease. In addition, an abdominal examination should be performed in patients with an empyema of unknown origin.